Thematic Analysis Human Rights in the Hadith: Legal Foundations and Philosophical Perspective in Islamic Law - Fitri Sari; Muhammad Mujib Baidhowi; Rizqa Amelia; Hanung Sito Rohmawati; Mujiburrohman Mujiburrohman (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
This article aims to explore and analyze human rights from the perspective of the Prophet Muhammad's hadith. In this context, the hadith serves as the second source of law in Islam after the Qur'an, examining both Islamic legal viewpoints and philosophical aspects to gain a more comprehensive understanding. The author argues that the concept of human rights in Islam shares several similarities with the concept of modern human rights, as well as some differences in terms of interpretation, sources, and emphasis on specific principles. This research employs a qualitative method with a literature study approach, utilizing Islamic law and philosophical perspectives. The findings of this article reveal that hadith addresses fundamental aspects that have implications for Islamic law related to human rights, including the right to property or wealth, freedom of religion, and justice. Furthermore, when interpreting hadith related to human rights philosophically, several meanings emerge, including universal equality and justice, social responsibility and solidarity, freedom of religion and concern for individual freedoms, law, justice, and individual rights, as well as human dignity. Through the hadith as a guide for Islamic teachings, a moral and ethical foundation, along with principles of justice and equality, is established, creating a robust basis for inclusivity, empathy, and social responsibility in the context of human rights.